Steatohepatitis-Like Changes in Hepatocellular Adenoma: A Clinical and Pathological Study. Issue 4 (20th June 2020) - Liu, Yongjun; Zen, Yoh; Yeh, Matthew M
Abstract: Objectives: Our aim was to investigate the frequency of steatohepatitic morphology in hepatocellular adenoma (HCA) and correlate with its clinical parameters and risk factors underlying nonalcoholic fatty liver disease (NAFLD) or nonalcoholic steatohepatitis (NASH). Methods: We examined a series of 41 liver resection specimens diagnosed with HCA for steatohepatitic changes. Background nonneoplastic liver was also evaluated. Clinical records were reviewed for risk factors of NAFLD/NASH. Results: Six steatohepatitic HCAs (SH-HCAs) were identified, with an overall prevalence of six (14.6%) of 41, of which three were HNF1α inactivated and three were inflammatory, but none were β-catenin mutated. Five of the six patients with SH-HCA had at least one known risk factor for NAFLD/NASH, including obesity (n = 4; 66.7%), diabetes (n = 5; 83.3%), hypertension (n = 3; 50%), and dyslipidemia (n = 1; 16.7%). Compared with the patients without SH-HCA, the patients with SH-HCA had a higher frequency of type 2 diabetes, obesity, and hypertension. Of the six SH-HCAs, background nonneoplastic liver showed significant steatosis in three (50%) cases and steatohepatitic changes in one (16.7%) case. Conclusions: Approximately 15% of HCAs in our series demonstrated steatohepatitic changes. Lack of such morphology in β-catenin–mutated subtype suggests reassurance in this morphologic variant of HCA.